FONDASI EKONOMI ISLAM DAN DINAMIKA KEKUASAAN KERAJAAN ISLAM AWAL (ABAD XIII–XVII): PENDEKATAN PENDIDIKAN SEJARAH SAMUDERA PASAI, MALAKA, DAN ACEH DARUSSALAM - Husnaini; Zulfikar; Bobby Fahreza; Muhammad Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the strategic role of the Islamic kingdoms of the early 13th–17th centuries in shaping the foundations of the economy, power, and civilization of the Indonesian archipelago, which has not been fully studied through a historical education approach. This research aims to analyze the relationship between the foundations of Islamic economics and the dynamics of the ebb and flow of power of the Samudera Pasai, Malacca, and Aceh Darussalam Kingdoms and their relevance for the development of history learning. The method used is qualitative research with a descriptive-analytical character through a historical approach and history education, using secondary data sourced from historical chronicles, legal manuscripts, traveler's notes, as well as scientific literature and reputable journals. The research findings show that an Islamic economy based on international trade, port governance, currency, the Baitul Mal (the Islamic treasury), and religious legitimacy formed the primary basis for the formation and strengthening of the power of these three kingdoms. Samudera Pasai emerged as a pioneer of Islamic economics and education, Malacca as the center of maritime hegemony and Islamic law, while Aceh Darussalam developed as a political, economic, and intellectual power oriented toward colonial resistance. The research findings confirm that the decline of these kingdoms was influenced by internal conflict and global geopolitical pressures. The implications of this research enrich the historiography of Islam in the Indonesian archipelago while providing a practical contribution to history education through the development of contextual, critical teaching materials that are rich in economic values, power, and Islamic-national identity.